Transition metal complexes of novel binuclear Schiff base derived from 3, 3′-diaminobenzidine: synthesis, characterization, thermal behavior, DFT, antimicrobial and molecular docking studies. Issue 6 (18th March 2020) - Radha, Venkittapuram Palaniswamy; Chitra, Subramanian; Jonekirubavathi, Suyambulingam; Chung, Ill-Min; Kim, Seung-Hyun; Prabakaran, Mayakrishnan
Abstract: A series of binuclear Co(II), Ni(II), Cu(II), and Zn(II) complexes were prepared with a novel bidentate Schiff base ligand derived by condensation of 3, 3′-diaminobenzidine with creatinine. The prepared compounds were characterized by elemental analysis, magnetic susceptibility measurements, molar conductivity, FT-IR, UV-vis, 1 H NMR, 13 C NMR and mass spectra and thermal analysis (TGA/DTG). From spectral analysis, an octahedral geometry was proposed for the complexes except Zn(II) complex which had tetrahedral geometry. The microcrystalline nature of the complexes has been confirmed by powder XRD and SEM analyses. The molecular structures of the Schiff base L and its Zn(II) complex were fully optimized and also their quantum chemical parameters were calculated. The synthesized ligand and their metal complexes were screened against two gram-positive, gram-negative bacterial and fungal species. The results revealed that the metal complexes exhibited higher antimicrobial activity than the free ligand. The antioxidant activity of the synthesized ligand and their metal complexes was carried out by DPPH method. Graphical Abstract: